1997
DOI: 10.2116/analsci.13.supplement_333
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Selectivity of an Electrochemiluminescence Pt Electrode Coated with a Ru(bpy)32+-Modified Chitosan/Silica Gel Membrane.

Abstract: The substrate selectivity of the known Ru(bpy)32+ eleetrochemiluminescence (ECL) is changed by coating a Pt working electrode with a Ru(bpy)32+-modified chitosan membrane and successively with a silica gel membrane that was prepared by the sol-gel method using tetramethoxysilane as a precursor. The double coating resulted in a high selectivity toward oxalic acid at pH 6.8, lowering relative ECL responses to trimethylamine, proline and 4-hydrox.yproline about 2.8, 3.4 and 3.8 times, respectively, compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…13,14 Although the immobilisation of Ru(bpy) 3 2+ in chitosan (CHIT) showed an improved stability, the CHIT film has a drawback of slow mass transfer through the film. 17,18 Lately the immobilised Ru(bpy) 3…”
Section: +mentioning
confidence: 99%
“…13,14 Although the immobilisation of Ru(bpy) 3 2+ in chitosan (CHIT) showed an improved stability, the CHIT film has a drawback of slow mass transfer through the film. 17,18 Lately the immobilised Ru(bpy) 3…”
Section: +mentioning
confidence: 99%
“…The detection limit, calculated from three times the standard deviation of the blank signal, was 3 3 10 27 M and a log-log plot of the data revealed that the response approximated linearity with a slope of 0.96. There have been a number of papers concerning the immobilisation of [Ru(bipy) 3 ] 2+ by either adsorption [3][4][5][6] or chemical bonding [7][8][9][10][11][12][13] for analytical chemiluminescence and seven of these have reported 3,6-9,12,13 limits of detection for sodium oxalate with only three 3,12,13 utilising FIA (see Table 2) with which, the unoptimised results achieved in this investigation compared quite favourably.…”
Section: Synthesis Of Cis-dichlorobis(22a-bipyridyl)ruthenium(ii)mentioning
confidence: 78%
“…1 One of the limitations to the more widespread analytical utility of this type of chemiluminescence is the wastage of this relatively expensive reagent following each determination. 2 Given the intrinsic facility for recycling this reagent, 2 a number of groups have sought to address the problem by investigating either the adsorption [3][4][5][6] or chemical immobilisation [7][8][9][10][11][12][13] of the [Ru(bipy) 3 ] 2+ . Immobilised [Ru(bipy) 3 ] 2+ has also been utilised for a variety of applications other than chemiluminescence detection.…”
Section: Introductionmentioning
confidence: 99%
“…ECL experiments were carried out using the same apparatus as reported previously 6,10 at room temperature; the potential applied to the photomultiplier was 900 V. The thickness of the membranes on the working electrode was determined by a Surfcom 575A surface texture measuring instrument (Tokyo Seimitsu Co., Japan).…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…We have recently prepared a Pt electrode coated doubly with Ru(bpy) 3 2+ -modified chitosan and silica-gel layers, which has been successfully applied to an ECL optic sensor with improved selectivity toward oxalic acid. 10 In the present paper we report on the fundamental behaviors, such as the potential dependence and the decay of the responses.…”
mentioning
confidence: 97%